Amperometric Biosensor Based on Coimmobilization of Multiwalled Carbon Nanotubes and Horseradish Peroxidase-Gold Nanocluster Bioconjugates for Detecting H2O2. (11th July 2020) - Ren, Qiong-Qiong; Yang, Fen; Ren, Wu; Wang, Chang; Jiang, Wen-Shuai; Zhao, Zong-Ya; Chen, Jun; Lu, Xuan-Yi; Yu, Yi
Abstract : An enzyme-based amperometric biosensor was fabricated for detecting hydrogen peroxide (H2 O2 ). Horseradish peroxidase (HRP) was modified using functionalized fluorescent gold nanoclusters (AuNCs) via biomineralization. HRP-AuNCs were successfully immobilized on multiwalled carbon nanotube- (MWCNT-) coated carbon fiber ultramicroelectrodes (CFUMEs). The AuNCs, which act as molecular electric wires, effectively promote the electron transfer between the enzyme active center and the electrode. Additionally, the HRP conjugated with the AuNCs retains its biological activity, which enables the catalytic reaction of H2 O2 . The HRP-AuNCs/MWCNTs/CFUMEs have been proven as excellent amperometric sensors for H2 O2 . The sensitivity of the H2 O2 biosensor is 3.0 × 10 − 4 A / M, and the detection limit is estimated to be 443 nM. Furthermore, the biosensor exhibited long-term stability and good reproducibility. Moreover, the biosensor has been tested by determining the H2 O2 concentration in calf serum samples.